2022
DOI: 10.1002/pca.3157
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characterisation by UPLC‐Q‐ToF‐MS/MS and antibacterial potential of Coffea arabica L. leaves: A coffee by‐product

Abstract: Introduction: Coffea arabica L. leaves are considered a by-product of the coffee industry however they are sources of several bioactive compounds.Objectives: This study aimed to evaluate the chemical composition and the in vitro antibacterial activity of the lyophilised ethanol extract of arabica coffee leaves (EE-CaL).Material And Methods: The chemical characterisation of EE-CaL was performed using ultra-performance liquid chromatography coupled to quadrupole time-of-flight mass spectrometry (UPLC-Q-ToF-MS/MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…This compound generated a fragment ion [M + H-COOH] + at m/z 94.0652. By comparing the mass spectrum information reported in the literature, the compound was confirmed as trigonelline ( Gilmar et al, 2022 ; Tatiane et al, 2019 ).…”
Section: Resultsmentioning
confidence: 81%
“…This compound generated a fragment ion [M + H-COOH] + at m/z 94.0652. By comparing the mass spectrum information reported in the literature, the compound was confirmed as trigonelline ( Gilmar et al, 2022 ; Tatiane et al, 2019 ).…”
Section: Resultsmentioning
confidence: 81%
“…The patent CA3067924A1 is a topical cream with a bactericidal component and various substances, such as green coffee bean extract, which revitalizes and restores the natural skin microbiota. Data from the literature widely report the antimicrobial potential of several compounds present in coffee, such as chlorogenic acids, caffeine, trigonelline, quinic acid, catechin, UM, melanoidins and mangiferin (described in coffee leaves) [29][30][31][32][33][34].…”
Section: Skinmentioning
confidence: 99%
“…The coffee industry generates a significant amount of by-products that can be used as a source of bioactive compounds [ 102 , 103 ]. Researchers have evaluated the antibacterial activity of arabica coffee leaves and found that the extracts contain the alkaloids trigonelline and caffeine [ 102 ]. These extracts were found to be effective against E. coli .…”
Section: Antibacterial Phytochemicals Identified In Food Wastesmentioning
confidence: 99%